(untitled) (Italiano LinguaDue, 2023)
The implementation of technologies in language learning classrooms has been accelerated by the Covid-19 pandemic, with a consequential boost in the evolution of educational methodologies towards blending in-person with remote teaching. Consequently, it is necessary that teachers are given opportunities to train their technological competences to conduct and manage an increasingly digitalized language learning environment. Despite the importance of digital approaches to language education, research on the impact of technologies on the teachers’ acceptance and endorsement of digital tools in educational settings are limited, especially with regards to teaching Italian as an L2. Therefore, this article bridges this gap by analyzing the potential implications of a technology-based methodological training on teachers’ adoption and implementation of technologies in educational contexts. It presents the results of a mixed-methods investigation conducted on a group of Italian L2 teachers taking a four-weeks training course on educational technology. Teachers took pre- and post-course TAM tests (Davis, 1989) and participated to online focus groups. Results confirmed the successful impact of the training course on teachers’ acceptance of digital tools and practices. However, the positive effects of technology use on the linguistic competence of Italian L2 students was debated by the teachers. By further investigating survey and focus group responses, this article provides evidence for encouraging teachers’ integrations of technologies in Italian L2 educational contexts. L’impatto sulla loro usabilità e accettazione da parte degli insegnanti di italiano come lingua straniera di una formazione post-pandemica sulle tecnologie didattiche L’uso delle tecnologie digitali nelle classi di lingua straniera ha subito un’accelerazione con la pandemia di Covid-19, con una conseguente evoluzione di metodologie glottodidattiche ibride che combinano l’insegnamento da remoto con quello in presenza. È diventato dunque necessario sostenere la formazione tecnologica di insegnanti per permettere loro di gestire e condurre lezioni di lingua. Nonostante l’importanza di approcci digitali alla didattica linguistica, poche ricerche sono state dedicate all’impatto delle tecnologie sull’accettazione e l’utilizzo di strumenti digitali da parte di docenti, specialmente per quanto riguarda l’insegnamento dell’italiano L2. Per cercare di colmare tali lacune, questo articolo presenta i risultati di un’indagine sull’accettazione e l’applicazione di strumenti digitali da parte di un gruppo di insegnanti di italiano L2 iscritti ad un corso di formazione sulle tecnologie educative. I docenti hanno risposto a questionari TAM (Davis, 1989) e partecipato a focus groups online. I risultati hanno dimostrato l’impatto positivo del corso sui livelli di accettazione e di pratica didattica con le tecnologie da parte degli insegnanti, che hanno però aperto un dibattito riguardo ai benefici delle tecnologie digitali sulle competenze linguistiche di studenti di italiano L2. Attraverso l’analisi delle risposte degli insegnanti ai questionari e alle interviste, l’articolo evidenzierà l’importanza di favorire l’integrazione delle tecnologie digitali in contesti di glottodidattica dell’italiano L2.